The Road Performances Analysis in Jalan Yos Sudarso, Batam-Indonesia - Kurnia Gilang Ramadani; Yusra Aulia Sari (Fakultas Teknik Sipil dan Perencanaan, 2023)
Traffic congestion is a global problem, including Indonesia, the 4th most populous country. Jalan Yos Sudarso is an arterial road with high vehicle intensity. This road is close to the industrial area and often experiences congestion during peak hours. This study aims to determine the performance of Jalan Yos Sudarso. This research was conducted directly by surveying the field on May 17, 2023, from 07.00 - 08.00 AM to collect data. Data collection was carried out on Jalan Yos Sudarso. The results obtained from traffic analysis are total volume = 3599.4 pcu/hour, capacity = 6468. Degree of saturation = 0.56 and Level of Service = C. From these results, Jalan Yos Sudarso is still comfortable passing.